NT2-derived astrocyte–neuron co-culture reflects physiological relevance and offers research validity - Sylwia Kedracka-Krok; Ewelina Fic; Zuzanna Cepil; Piotr Rybczyński; Agata Szlaga; Radosław Cacała; Sławomir Lasota; Anna Blasiak; Marta Dziedzicka-Wasylewska (Cellular & Molecular Biology Letters)
Abstract Background Obtaining human neurons and astrocytes for in vitro studies presents a significant challenge owing to the complexity of replicating their development and functionality outside the human brain. The Ntera-2 cell line is a valuable source of human neurons and astrocytes in neuroscience research. However, differentiating Ntera-2 cells into neurons and astrocytes with all-trans retinoic acid is complicated by the lack of reliable markers to monitor differentiation stages effectively. This study aimed to characterize neuron-enriched and pure astrocyte cultures at two maturation stages and to compare these with the original Ntera-2 cells. Ntera-2 cells and NT2 cells are used interchangeably in this publication. Methods Using an advanced proteomic approach, we assessed the protein composition and abundance of neuron and astrocyte co-cultures and discovered that the astrocytic protein profile in co-culture with neurons was more representative compared with that in pure astrocyte cultures. Additionally, electrophysiological studies were conducted to investigate the best astrocyte content for neuronal functionality. Results Mass spectrometry-based analysis provided insights into over 9000 proteins, covering well-known protein markers, proteins unique to specific cell types, and differentially expressed proteins. Notably, differences in transcription factors, regulatory proteins, intermediate filaments, and proteins unique to early and mature astrocytes highlighted the distinct maturation, activation, and functional profiles of the various cells. These findings offer a straightforward tool for characterization and monitoring the differentiation process. Three weeks of maturation in pure culture yielded immature astrocytes; however, extending the maturation period to 6 weeks significantly altered the composition of the cellular proteome, indicating increased astrocyte maturity. Studies revealed a broader repertoire of astrocytic proteins in co-culture with neurons. Meanwhile, electrophysiological analyses demonstrated that a high content of astrocytes is essential for neuronal functional maturity. Conclusions Astrocyte–neuron co-cultures offer a more accurate model of neural tissue than pure cultures, highlighting the complexity of cell maturation and providing insights for improving in vitro modeling of human neural development. Graphical Abstract